Topology and shape optimization of continuum structures by genetic algorithm and BEM - Kita, Eisuke; Tamaki, Tatsuhiro; Tanie, Hisashi (Computer Assisted Methods in Engineering and Science, 2023)
This paper describes the topology and shape optimization scheme of continuum structures by using genetic algorithm (GA) and boundary element method (BEM). The structure profiles are defined by using the spline function surfaces. Then, the genetic algorithm is applied for determining the structure profile satisfying the design objectives and the constraint conditions. The present scheme is applied to minimum weight design of two-dimensional elastic problems in order to confirm the validity.